2019
DOI: 10.1007/s00417-018-04213-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ranibizumab 0.5 mg in Chinese patients with visual impairment due to diabetic macular edema: results from the 12-month REFINE study

Abstract: Purpose To demonstrate the efficacy and safety of ranibizumab 0.5 mg pro re nata (PRN) versus laser photocoagulation for the treatment of Chinese patients with visual impairment due to diabetic macular edema (DME). Methods REFINE was a phase III, 12-month, double-masked, multicenter, laser-controlled study in patients (aged ≥ 18 years) with DME. Patients were randomized 4:1 to receive either ranibizumab 0.5 mg or laser dosing regimen. Efficacy was evaluated as mean average change in best-corrected visual acuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…The REFINE was a phase III, 12-month, double-masked, multicenter, laser-controlled study conducted on Chinese patients with DME. Patients were randomly assigned (4.1) to receive intravitreal ranibizumab injections or laser [ 64 ]. The mean BCVA improvement with ranibizumab at month 12 (+7.9 letters) was statistically significantly greater ( p < 0.001) than that observed with laser (+2.5 letters) [ 64 ].…”
Section: Treatment Strategies Of Dmementioning
confidence: 99%
See 2 more Smart Citations
“…The REFINE was a phase III, 12-month, double-masked, multicenter, laser-controlled study conducted on Chinese patients with DME. Patients were randomly assigned (4.1) to receive intravitreal ranibizumab injections or laser [ 64 ]. The mean BCVA improvement with ranibizumab at month 12 (+7.9 letters) was statistically significantly greater ( p < 0.001) than that observed with laser (+2.5 letters) [ 64 ].…”
Section: Treatment Strategies Of Dmementioning
confidence: 99%
“…As regards the safety profile, the incidence and characteristics of the adverse events were similar to that observed with bevacizumab. Systemic VEGF inhibition-related adverse events such as stroke and myocardial infarction have been described with the administration of ranibizumab [ 45 64 ]. The most commonly reported ocular adverse event among the different studies was conjunctival hemorrhage.…”
Section: Treatment Strategies Of Dmementioning
confidence: 99%
See 1 more Smart Citation
“…Most studies found anti-VEGFs to be superior to laser treatment in DME patients. The REFINE study was conducted in Chinese patients with DME who received intravitreal ranibizumab injections or LP [27]. The results revealed a significantly greater improvement in mean best-corrected visual acuity (BCVA) at month 12 with ranibizumab than with LP [27].…”
Section: Diabetic Macular Edemamentioning
confidence: 99%
“…The REFINE study was conducted in Chinese patients with DME who received intravitreal ranibizumab injections or LP [27]. The results revealed a significantly greater improvement in mean best-corrected visual acuity (BCVA) at month 12 with ranibizumab than with LP [27]. Singh and colleagues reported that BCVA improvement was significantly greater with aflibercept than with laser techniques and was not influenced by any baseline factors [28,29].…”
Section: Diabetic Macular Edemamentioning
confidence: 99%